Main factors of adherence to new oral anticoagulants and its dynamics in outpatients with nonvalvular atrial fibrillation: results of the ANTEY study - Yu. V. Lukina; N. P. Kutishenko; S. N. Tolpygina; V. P. Voronina; N. A. Dmitrieva; O. V. Lerman; N. A. Komkova; A. V. Zagrebelny; S. Yu. Martsevich; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2020)
Aim. To assess adherence to new oral anticoagulants (NOAC) or warfarin therapy and to study the factors influencing adherence in nonvalvular atrial fibrillation (AF) patients on different stages of treatment within the prospective outpatient registry of patients with cardiovascular diseases.Material and methods. The study included 201 patients with nonvalvular AF (males, 118 (58,7%)) from the outpatient registry PROFILE). Mean age was 71,1 ±8,7 years. Study protocol consisted of the inclusion visit (V0), 6-month follow-up visit (V1) and phone contact 1 year after V0 (PC). In V0, all patients were prescribed one of the NOACs. At V1 doctors could recommend warfarin or another NOAC to patients, who have refused taking prescribed NOAC. Medical adherence was determined using the of the National society of evidence-based pharmacotherapy (NSEPh) adherence scale. NSEPh adherence scale allows to grade patients’ adherence to treatment into 4 categories: 1) completely adherent, 2) partially adherent, 3) completely non-adherent, 4) partially non-adherent. Dichotomous grading into adherent (completely adherent) and non-adherent (rest of patients) was also used.Results. Out of 201 included patients, 200 came to V1 (1 patient died). PC was successful in 197 patients (3 patients died). According to NSEPh adherence scale, 155 (77,5%) patients at V1 were completely adherent, 5 (2,5%) — partially adherent, 7 (3,5%) — partially non-adherent, 33 (16,5%) — completely non-adherent. By the PC, 158 (80,2%) patients were completely adherent to the OAC therapy, 6 (3,0%) — partially adherent, 28 (14,2%) — partially non-adherent, 15 (7,6%) — completely non-adherent. At all stages of treatment, the following factors of good adherence remained significant: never-smoking, prior NOAC use, negative history of any treatment-related adverse effects (AEs). Patients with comorbidities and a history of bleeding during OAC therapy were more likely to discontinue initial scheme and violate treatment regimen (p<0,05). Symptomatic course of AF increased adherence by 2,4 times (р=0,02). According to the questionnaire, the leading reasons for refusing NOAC therapy were the high cost of drugs, the fear of AE and doubts about the need for treatment. The main factors leading to discontinuation of NOAC/OAC treatment were bleeding and the cancellation (often unreasonable) of these medications by other doctors.Conclusion. The results of ANTEY study confirm that factors influencing adherence to NOAC may vary during different phases of treatment. The main reasons that prevent NOAC therapy initiation are the high cost of these drugs, fear of AE and doubts about the need for such treatment. Significant factors of discontinuation were AEs and cancellation of NOAC therapy by doctors from other medical institutions. Factors that positively affect both initiation and long-term use of the drug are never-smoking, prior NOAC use, negative history of any treatment-related AEs.